Risk Factors for Retinal Arteriolar Emboli in Coronary Artery Disease - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2009)
This study determined the prevalence of retinal arteriolar emboli risk factors in 148 patients (86 males) diagnosed with coronary artery disease who required coronary artery bypass graft surgery (mean +/- SD age 59.1 +/- 12.9 years). The prevalence of smoking was 50.7%, hypertension was 49.3%, diabetes mellitus was 27.0% and obesity was 31.1%. Retinal arteriolar emboli were detected using binocular indirect ophthalmoscopy of both eyes. They were found in 10 patients (6.8%) and identified as the cholesterol type. Patients were divided according to their baseline low-density lipoprotein cholesterol (LDL-C) serum level; retinal arteriolar emboli were significantly more frequent in patients with LDL-C levels > 100 mg/dl. These results demonstrate that the prevalence of hypercholesterolaemia and high LDL-C were increased in patients with retinal arteriolor emboli. Identification and treatment of modifiable risk factors, such as high LDLC and hypercholesterolaemia, might be beneficial in these individuals.
Keywords: CORONARY ARTERY DISEASE; RETINAL ARTERIOLAR EMBOLI; HYPERCHOLESTEROLAEMIA; LOW-DENSITY LIPOPROTEIN CHOLESTEROL (LDL-C); CARDIOVASCULAR RISK FACTORS; BEAVER DAM EYE; CARDIOVASCULAR HEALTH; CHOLESTEROL EMBOLI; MICROVASCULAR ABNORMALITIES; VEIN OCCLUSION; PREVALENCE; ASSOCIATIONS; STROKE